2014
DOI: 10.3991/ijet.v9i5.3911
|View full text |Cite
|
Sign up to set email alerts
|

Social Media: An Optimal Virtual Environment for Learning Foreign Languages

Abstract: Abstract-The present paper aims at exploring the potential role that social media technologies play in learning foreign languages. For this purpose, a survey was carried out to examine students' and language learners' perceptions and attitudes about using these platforms. Results of the research study revealed that the great majority of the respondents actually use these web-based applications to enhance their language skills. Most importantly, they noted that social media contribute in improving their listeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…It is therefore central to the development of students' critical thinking skills. Students' usage of the web-based applications has enhanced all of their language skills including reading, listening, speaking, and writing; thus social media is seen as the optimal virtual environment for language acquisition (Faizi, El Afia, & Chiheb, 2014). On the other hand, four active participants, did not improve in their language skills, but felt a boost of self-confidence to use English in more public spaces.…”
Section: 24mentioning
confidence: 98%
“…It is therefore central to the development of students' critical thinking skills. Students' usage of the web-based applications has enhanced all of their language skills including reading, listening, speaking, and writing; thus social media is seen as the optimal virtual environment for language acquisition (Faizi, El Afia, & Chiheb, 2014). On the other hand, four active participants, did not improve in their language skills, but felt a boost of self-confidence to use English in more public spaces.…”
Section: 24mentioning
confidence: 98%
“…Research shows that students recognize didactic use of Web 2.0 technologies (Faizi et al, 2014;Lai et al, 2017;Steel & Levy, 2013;Wang & Vasquez, 2012) and actively use technological resources beyond their FL classroom environment. In a survey study with university students in Morocco, Faizi et al (2014) found that most of the respondents already use social media applications to enhance their four language skills: listening, speaking, reading and writing skills. Steel and Levy (2013) found that undergraduate FL students in an Australian university preferred to use discipline-specific technologies to acquire the basics of language.…”
Section: Kuznetsova and Soomromentioning
confidence: 99%
“…Chang, Pearman, and Farha (2012) highlight that the technological mediation of foreign language is beneficial for students who experience shyness and language barrier, and Web 2.0 allows learners engage with multiple native speakers in different contexts. Similarly, Faizi, Afia, and Chiheb (2014) propose that Web 2.0 technologies offer learners wider opportunities to practice their language and communication skills outside the formal learning environment. Among the returns of the use of online technologies in foreign language learning, Pop (2010) stresses "connectivity, diversity of experiences and needs, instant response and feedback", as well as a variety of modes of interaction and flexibility (P. 52).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore recommended that the design of virtual games be integrated into e-learning materials to improve its impact on multiple intelligence development. Social media is also a suitable avenue for e-learning materials since it has the most number of users in agreement to Faizi et al [15] who recommended online tools in distant, blended, or face-to-face language learning settings. Moreover, adding educational games to virtual e-learning materials will also add to its impact on learning.…”
Section: Conclusion and Recommendationmentioning
confidence: 56%